Thermal and Morphological Studies on Bismaleimide Modified ZnO Nanoparticles - Vadivel, M.; Suresh Chandra kumar, M.; Selvam, V.; Shobana, Sutha; Arvind Narayan, S. (Asian Journal of Chemistry, 2014)
The bismaleimide (N,N'-bismaleimide-4,4'-diphenylmethane) (BMI) modified siliconized zinc oxide nanoparticles were prepared in chloroform. The FT-IR spectroscopy analysis of BMI/ZnO reveals that -NH2 groups of siliconized ZnO reacts with the maleimide double bond of bismaleimide molecules through a nucleophilic (Michael) addition reaction. The thermal (TG) and morphological properties of bismaleimide modified zinc oxide nanoparticles (BMI/ZnO), were investigated. The particle size and morphology of zinc oxide nanoparticles and siliconized zinc oxide nanoparticles were determined by XRD. The SEM images indicate that the diameter of the zinc oxide nanoparticles is in the range of 25-40 nm with a strong aggregation process. It is observed that aggregates of bismaleimide modified siliconized zinc oxide nanocomposites of different size and shape are heterogeneously distributed in the elastomeric surface due to the low shear stress and processing time, which do not make an exfoliated material.